(untitled) (Journal of Economic Research & Business Administration, 2015)
The article deals with the problem of the functioning of the various forms of management, in turn, form the mixed economy. Attention is paid to the authors not only economic aspects, but also the legal issues of formation of promising forms of entrepreneurship in the agricultural sector of Kazakhstan.